A salt-resistant foam drainage agent for natural gas exploitation and preparation method thereof
By combining modified amine oxide with hollow silica balls, urea decomposition is used to generate bubbles and achieve sustained release through the pores, the problem of the lack of significant effect of traditional foam drainage agents in the later stage of natural gas mining is solved, significantly enhancing the drainage effect and extending the use cycle.
Patent Information
- Application Number
- CN202411906869.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-24
AI Technical Summary
The traditional foam drainage agent has no significant effect in the later stage of natural gas mining, and it consumes fast, making it difficult to effectively remove fluid accumulation in the gas well, resulting in a decrease in gas production and equipment corrosion.
The modified amine oxide is combined with the silica hollow sphere, and the urea structure of the modified amine oxide is decomposed at the gas well temperature to generate bubbles, and the sustained release of the modified amine oxide and the effective treatment of the effusion is achieved through the pores of the silica hollow sphere.
It significantly enhances the effect of foam drainage agent, extends the service cycle, improves the processing capacity of fluid accumulation, ensures stable production of gas wells and reduces the risk of equipment corrosion.
Smart Images

Figure CN119351073B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of foam drainage agents, and more specifically, to a salt-resistant foam drainage agent for natural gas exploitation and a preparation method thereof. Background Art
[0002] Foam drainage agent refers to a surfactant used to improve the properties of the interface between liquid and gas. Its molecular structure is similar to that of soap molecules. It can reduce the surface tension of liquid by forming foam, so that gas forms foam on the liquid surface. According to the type, it can be divided into liquid foam drainage agent and solid foam drainage agent. Among them, solid foam drainage agent is more used in the field of oil and gas production due to its strong environmental adaptability and better foaming effect.
[0003] For natural gas extraction, in the early stage of gas well extraction, due to the sufficient natural gas source, the groundwater in the gas well can be completely discharged from the gas well in the form of gas-carrying liquid, and will not block the gas well. However, in the later stage of extraction, due to the pressure drop in the gas well and the reduction of gas production, the groundwater in the gas well is difficult to be completely removed, and the undischarged groundwater is deposited at the bottom of the gas well, resulting in liquid accumulation. The accumulation of liquid accumulation will reduce the gas phase permeability of the gas well and inhibit the flow of natural gas, resulting in a rapid decrease in gas production. At the same time, inorganic salts and acidic and alkaline substances accumulated in the liquid accumulation will also corrode the pipeline, resulting in a reduction in equipment life. The addition of foam drainage agent can alleviate the problem of liquid accumulation, and by reducing the surface activity of the liquid accumulation, the liquid accumulation can be more easily discharged from the gas well. However, traditional foam drainage agents have the disadvantages of weak effect and fast consumption, and their effect is not significant.
[0004] The Chinese patent application document with application publication number CN117777985A discloses a bubble net synergistic solid foam drainage agent and its preparation method, which introduces a bubble net structure made of a soluble support material and coats the bubble net structure on the surface of the solid foam drainage agent. When in use, the outer coated bubble net structure dissolves, thereby gradually exposing the solid foam drainage agent inside, avoiding the foam drainage agent from directly and violently interacting with the effusion, and extending the use time of the solid foam drainage agent.
[0005] Although the above application documents can slow down the consumption rate of the foam drainage agent, they will also reduce the effect of the foam drainage agent per unit time. Therefore, there is still a need to find a foam drainage agent that has both a slow-release effect and can also enhance the effect of the foam drainage agent. Summary of the invention
[0006] In order to obtain a foam drainage agent product that has both a slow-release effect and can also enhance the effect of the foam drainage agent, the present application provides a salt-resistant foam drainage agent for natural gas exploitation and a preparation method thereof.
[0007] In a first aspect, the present application provides a method for preparing a salt-resistant foam drainage agent for natural gas exploitation, comprising the following steps:
[0008] (1) Dissolving the modified amine oxide, mixing it with the hollow silica spheres, treating it under reduced pressure for 0.5-1 h, and allowing it to stand at normal pressure to obtain a mixture, which is recorded as M;
[0009] (2) Crush the glass fiber, disperse it in chloroform, mix it with No. 58 paraffin, treat it at 75-80℃ for 10-30min, add the mixed cross-linking agent, stir it for 2-2.5h, keep it at 60-65℃ to obtain the sealing liquid, filter M to get the precipitate, mix it with the sealing liquid, let it stand for 0.5-1h, filter the precipitate again, and after cooling, obtain the anti-salt foam drainage agent for natural gas development.
[0010] By adopting the above technical scheme, the modified amine oxide has the structure of both amine oxide and urea. The amine oxide plays a role in reducing the surface tension of the accumulated liquid in the system. Urea can be decomposed under the temperature environment of the gas well and produce more bubbles under the action of the composite structure, thereby enhancing the effect of the foam drainage agent. The silica hollow sphere is a carrier of the modified amine oxide. On the one hand, the pores on the surface are the channels for the release of the modified amine oxide. With the subsequent glass fiber mesh structure, the slow release effect of the modified amine oxide can be achieved, thereby enhancing the service life of the modified amine oxide component. At the same time, the accumulated liquid can also directly react with the internal modified amine oxide through the pores of the silica hollow sphere to form bubbles. The bubbles generated can form denser bubble clusters after being constrained by the pores of the silica hollow sphere, thereby enhancing the treatment effect of the accumulated liquid.
[0011] Preferably, in the step (1), the mass ratio of hollow silica spheres to injection liquid is 1:(5-7.5).
[0012] By adopting the above technical solution and using hollow silica spheres and injection liquid of the above mass ratio, it can be ensured that the hollow silica spheres are filled with the injection liquid after the reduced pressure and normal pressure static treatments.
[0013] Preferably, in the step (1), the reduced pressure is 0.01-0.03 MPa.
[0014] Preferably, in step (2), the mixed cross-linking agent is a mixture of diphenylmethane diisocyanate and tricresyl phosphite in a mass ratio of 5:1.
[0015] By adopting the above technical scheme, the surface silanol of the glass fiber reacts with the isocyanate group in the mixed crosslinking agent, the chloroform dissolves the chopped glass fibers and mixes and disperses them with paraffin wax, and under the action of the mixed crosslinking agent, the chopped glass fibers dispersed in the paraffin wax are crosslinked with each other and interwoven into a network. After being added to the precipitate in M, the silica balls in the precipitate are wrapped by the paraffin wax to form a cluster structure, and the chopped glass fibers dispersed in the paraffin wax continue to react with this as a crosslinking template, and finally a chopped glass fiber grid is obtained on the surface of the silica balls.
[0016] In a second aspect, the present application provides a salt-resistant foam drainage agent for natural gas exploitation, wherein the preparation steps of the modified amine oxide are as follows:
[0017] (S01) Mix a brominated alkyl source and dipropylamine, dissolve them, react at 55-65°C for 5-8h, add sodium carbonate, stir, filter out the liquid, dropwise add hydrogen peroxide solution, react at 70-85°C for 1-2h, then rotary evaporate, take the bottom viscous liquid, wash and obtain brominated amine oxide;
[0018] (S02) mixing brominated amine oxide with urea, dissolving in a mixed solvent, reacting at 55-70° C. for 5-7 hours, distilling, and washing with alcohol to obtain a modified amine oxide;
[0019] The preparation steps of the hollow silicon dioxide spheres are as follows:
[0020] (I) Mixing ethyl orthosilicate with a mixed template solution, stirring at 60-65°C, adding a dilute acid solution dropwise, reacting, adding anhydrous ethanol, stirring to obtain a sol solution, and then dropping it dropwise into tetrahydrofuran, with a water bath temperature of 53-60°C, standing for 8-15 hours, filtering and drying to obtain silica beads;
[0021] (II) Calcine and acid-etch the silica beads to obtain hollow silica spheres.
[0022] Preferably, in the step (S01), the alkyl bromide source is obtained by mixing 1,2-dibromododecane, 1,3-dibromotetradecane and 1,10-dibromooctadecane in a mass ratio of 1:1.5:(2.5-3); and the mass ratio of the alkyl bromide source to dipropylamine is 1:(0.67-0.8).
[0023] By adopting the above technical solution, the alkyl bromide source reacts with dipropylamine to obtain a tertiary amine intermediate. The use effect of the tertiary amine intermediate obtained by using the above alkyl bromide source and proportion is the best.
[0024] Preferably, in the step (S01), the mass concentration of the hydrogen peroxide solution is 10%-15%.
[0025] By adopting the above technical solution, the oxidation reaction of hydrogen peroxide and the tertiary amine intermediate mainly occurs at the tertiary amine site. Since the N atom of the tertiary amine has a higher electron cloud density, it is more susceptible to the attack of the nucleophilic reagent hydrogen peroxide and undergoes an oxidation reaction, ultimately obtaining an oxidized amine structure. By regulating the mass concentration of hydrogen peroxide, it is possible to avoid the situation where the hydrogen peroxide reaction violently destroys the bromine group on the tertiary amine intermediate.
[0026] Preferably, in the step (S02), the mixed solvent is prepared by mixing acetonitrile, potassium carbonate and pyridine in a mass volume ratio of (50-100) mL: (1.5-2) g: (1.5-2.5) g.
[0027] By adopting the above technical scheme, acetonitrile is a good solvent for the reaction, the reaction occurring in the system is nucleophilic substitution of the amino group on the urea with the bromoalkane, the resulting amide structure, and HBr is removed at the same time, potassium carbonate and pyridine are acid binding agents of the reaction system, which can effectively remove HBr generated in the reaction and promote the forward progress of the reaction.
[0028] Preferably, in the step (I), the mixed template solution is prepared by mixing sodium hexametaphosphate, Tween 20, soybean lecithin and carboxymethyl cellulose in a mass volume ratio of (1-2) g: (0.2-0.3) mL: (1.03-1.25) g: (0.5-0.73) g.
[0029] By adopting the above technical solution, soybean lecithin is used as an organic vesicle template and is mixed with tetraethyl orthosilicate, so that the vesicle template can be distributed between the cross-linked structures when tetraethyl orthosilicate is hydrolyzed. In the subsequent calcination operation, soybean lecithin decomposes to produce gas and residual carbon, and constructs a cavity and pore structure in the silica beads. Tween 20 is a non-ionic surfactant, which helps to form droplets with larger particle size by reducing the surface tension of the sol.
[0030] Preferably, in step (I), the amount of anhydrous ethanol added is controlled to be 10-20 mL.
[0031] Preferably, in the step (II), the calcination includes primary calcination, cooling, and secondary calcination, and the operation is as follows:
[0032] Primary calcination: raise the temperature in the muffle furnace to 300-350°C at a rate of 5-8°C / min and keep it at that temperature for 20-30 minutes;
[0033] Cooling: Take the solid material out of the muffle furnace and cool it down naturally to 45-50℃;
[0034] Secondary calcination: add the solid material back into the muffle furnace at a rate of 10-15°C / min, raise the temperature to 600-750°C, and then keep the temperature constant for 2-3 hours.
[0035] By adopting the above technical solution, the purpose of the first calcination is to promote the decomposition of soybean lecithin on the surface of the silica beads. The phospholipids are distributed in the cross-linked network of the silica beads. The phospholipids located in the outer layer of the beads react before the internal phospholipids and slowly decompose during the first calcination, thereby leaving pre-holes on the surface of the silica beads. The presence of the pre-holes can also relieve the pressure of gas merging and expansion when the phospholipids inside the silica beads decompose during the second calcination process, thereby avoiding the breakage of the silica balls. The silica cavity structure can be obtained by calcination.
[0036] Preferably, in the step (II), the acid etching operation is: using hydrofluoric acid with a molar concentration of 0.05 mol / L for 10-30 min.
[0037] By adopting the above technical solution, the acid etching effect on the silica beads is best when the hydrofluoric acid of this concentration and the treatment time are used. The acid etching can trim the pores of the silica hollow spheres, so that the use effect of the silica hollow spheres is optimal.
[0038] In summary, this application has the following beneficial effects:
[0039] 1. The present application adopts modified amine oxide as a foam drainage agent component, which can reduce the surface tension of the effluent, and at the same time, the modified amine oxide itself generates foam, thereby enhancing the effect of the foam drainage agent. Silica is used as a carrier of the modified amine oxide in the foam drainage agent component. On the one hand, the pores on its surface are channels for the release of the modified amine oxide, and the amine oxide can be slowly released outward through the channels. At the same time, the effluent can also directly react with the internal modified amine oxide through the pores to generate foams. The generated bubbles can form denser bubble clusters after being constrained by the pores, thereby enhancing the foaming effect.
[0040] 2. The anti-salt foam drainage agent for natural gas development prepared in this application also has a long service life. Through the paraffin film, it can effectively isolate the outside air, and prevent the internal modified amine oxide from being exposed to the air and slowly deliquescing and losing. When it is put into the gas well, at the higher temperature in the gas well, the paraffin wrapped outside is melted and removed, and the remaining fiber grid structure cooperates with the silicon dioxide hollow ball to enhance the slow release effect of the product.
[0041] 3. The anti-salt foam drainage agent for natural gas exploitation prepared by the present application has a foaming and drainage performance drop of ≤4.5% before and after aging, and has relatively stable anti-heat aging performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 This is a TEM image of the hollow silica spheres prepared in Example 3 of the present application.
[0043] Figure 2 This is a SEM scanning electron microscope image of the hollow silica spheres prepared in Example 3 of the present application.
[0044] Figure 3 It is a schematic diagram of the foaming force height data before and after heat aging of Examples 1-3 and Comparative Examples 1-2 of the present application.
[0045] Figure 4 This is a schematic diagram of the liquid carrying capacity data before and after thermal aging of Examples 1-3 and Comparative Examples 1-2 of the present application. DETAILED DESCRIPTION
[0046] Example 1
[0047] The preparation method of the salt-resistant foam drainage agent used in natural gas development in this embodiment is as follows:
[0048] (1) Add 25 mL of ethylene glycol to 45 g of modified amine oxide, control the temperature to 45 °C, mix well, then add 0.1 g of ammonium dihydrogen phosphate and 0.5 g of dodecyl dimethyl amine oxide, mix to obtain an injection solution. Mix 60 g of the injection solution with 8 g of hollow silica balls, then depressurize the container to 0.01 MPa, adjust the magnetic stirring speed to 50 rpm, treat for 0.5 h, return to normal pressure, and let stand for 10 min. The resulting mixture is recorded as M.
[0049] (2) Take 8g of glass fiber and add it to a high-speed crusher, control the speed to 1000r / min, crush for 10min, and obtain chopped glass fiber. Use 15mL of chloroform to disperse the chopped glass fiber, mix it with 45g of No. 58 paraffin wax, heat it to 75℃, and treat it for 10min. Control the magnetic stirring speed to 25rpm, continue stirring for 10min, then add 3.5g of mixed cross-linking agent, increase the stirring speed to 75rpm, continue stirring for 2h, then lower the temperature to 60℃ and keep it constant to obtain the sealing liquid. Filter the precipitate of M and add it to the sealing liquid, let it stand for 0.5h, filter the precipitate again, cool it naturally, wait for the paraffin on the surface of silica to solidify, remove the sticky paraffin, and obtain the anti-salt foam drainage agent for natural gas exploitation.
[0050] The preparation steps of the modified amine oxide in this embodiment are as follows:
[0051] (S01) Take 15g of bromoalkyl source, mix with 10g of dipropylamine, use 150mL of anhydrous ethanol as the reaction solvent, control the reaction time to 5h and the temperature to 55°C, and obtain a tertiary amine intermediate. Then, add 3.2g of sodium carbonate to the system, control the magnetic stirring speed to 100rpm, stir for 10min, filter, take the liquid part, and then add 35mL of 10% hydrogen peroxide solution by mass to the system at a rate of 5mL / min, control the reaction temperature to 70°C, the magnetic stirring speed to 100rpm, react for 1h, perform rotary evaporation, adjust the vacuum degree to 250mbar, the water bath temperature to 65°C, the rotation rate to 150rpm, treat for 1.5h, take the bottom viscous liquid, wash with toluene to remove impurities, and obtain brominated amine oxide.
[0052] (S02) Brominated amine oxide was mixed with 3 g of urea, 50 mL of mixed solvent was added, the temperature was controlled at 55 °C, the reaction was carried out for 5 h, and then the solvent was removed by distillation. The modified amine oxide was obtained after washing with alcohol.
[0053] The preparation steps of hollow silicon dioxide spheres in this embodiment are as follows:
[0054] (I) Mix 20 mL of tetraethyl orthosilicate with 12 mL of mixed template solution, raise the temperature to 60 ° C, stir at a magnetic stirring speed of 50 rpm, and stir for 5 minutes. Then, add 20 mL of a 2% dilute hydrochloric acid solution to the mixed solution at a speed of 10 mL / min, increase the stirring speed to 150 rpm for 3 minutes, and then add 10 mL of anhydrous ethanol and stir to obtain a sol solution. Put the sol solution into a rubber-tipped dropper, prepare a 250 mL beaker, pour 100 mL of tetrahydrofuran, add the sol solution dropwise to the tetrahydrofuran, maintain the water bath temperature at 53 ° C, let it stand for 8 hours, then wash with anhydrous ethanol, dry and filter to obtain silica beads with a diameter of 3 mm.
[0055] (II) The silica beads were transferred to a muffle furnace, and the temperature in the muffle furnace was raised to 300°C at a rate of 5°C / min, and kept at this temperature for 20 minutes. The solid matter was then taken out of the muffle furnace, and the temperature was naturally lowered to 45°C. The solid matter was then added back into the muffle furnace, and the temperature was finally raised to 600°C at a rate of 10°C / min, and then kept at this temperature for 2 hours to obtain a sintered product. The sintered product was then transferred to 50 mL of hydrofluoric acid with a molar concentration of 0.05 mol / L, and after being treated for 10 minutes, a silica hollow sphere was obtained.
[0056] Among them, glass fiber (average diameter 9 microns, aspect ratio 300:1) was provided by Tai'an Quanfeng Glass Fiber Co., Ltd. Paraffin wax No. 58 (article number: MF-0005) was provided by Jiangyin Mengfan Rubber & Plastic Trading Co., Ltd. The mixed crosslinking agent was a mixture of diphenylmethane diisocyanate and tritolyl phosphite in a mass ratio of 5:1. The bromoalkyl source was obtained by mixing 1,2-dibromododecane, 1,3-dibromotetradecane, and 1,10-dibromooctadecane in a mass ratio of 1:1.5:2.5. The mixed solvent was prepared by mixing acetonitrile, potassium carbonate, and pyridine in a mass volume ratio of 50mL:1.5g:1.5g. The mixed template liquid was prepared by mixing sodium hexametaphosphate, Tween 20, soybean lecithin, and carboxymethyl cellulose in a mass volume ratio of 1g:0.2mL:1.03g:0.5g.
[0057] Example 2
[0058] The preparation method of the salt-resistant foam drainage agent used in natural gas development in this embodiment is as follows:
[0059] (1) Add 25 mL of ethylene glycol to 50 g of modified amine oxide, control the temperature to 55 °C, mix well, then add 0.15 g of ammonium dihydrogen phosphate and 1 g of dodecyl dimethyl amine oxide, mix to obtain an injection solution. Mix 55 g of the injection solution with 9 g of hollow silica balls, then depressurize the container to 0.02 MPa, adjust the magnetic stirring speed to 50 rpm, return to normal pressure after 1 hour of treatment, and let stand for 25 minutes. The resulting mixture is recorded as M.
[0060] (2) Take 10g of glass fiber and add it to a high-speed crusher, control the speed to 1000r / min, crush for 15min, and obtain chopped glass fiber. Use 20mL of chloroform to disperse the chopped glass fiber, mix it with 50g of No. 58 paraffin wax, heat it to 80℃, and treat it for 25min. Control the magnetic stirring speed to 50rpm, continue stirring for 10min, then add 4g of mixed cross-linking agent, increase the stirring speed to 100rpm, continue stirring for 2.5h, then lower the temperature to 65℃ and keep it constant to obtain the sealing liquid. Filter the precipitate of M and add it to the sealing liquid, let it stand for 1h, filter the precipitate again, cool it naturally, wait for the paraffin on the surface of silica to solidify, remove the sticky paraffin, and obtain the anti-salt foam drainage agent for natural gas exploitation.
[0061] The preparation steps of the modified amine oxide in this embodiment are as follows:
[0062] (S01) Take 15g of bromoalkyl source, mix with 12g of dipropylamine, use 150mL of anhydrous ethanol as the reaction solvent, control the reaction time to 5h and the temperature to 55°C, and obtain a tertiary amine intermediate. Then, add 3.8g of sodium carbonate to the system, control the magnetic stirring speed to 100rpm, stir for 10min, filter, take the liquid part, and then add 35-mL of 10% hydrogen peroxide solution at a rate of 5mL / min to the system, control the reaction temperature to 75°C, the magnetic stirring speed to 100rpm, react for 1-2h, and then perform rotary evaporation, adjust the vacuum degree to 250mbar, the water bath temperature to 70°C, the rotation rate to 150rpm, and after treating for 1.5h, take the bottom viscous liquid, wash with toluene to remove impurities, and obtain brominated amine oxide.
[0063] (S02) Brominated amine oxide was mixed with 3.2 g of urea, 60 mL of mixed solvent was added, the temperature was controlled at 55 °C, the reaction was carried out for 6 h, and then the solvent was removed by distillation. The modified amine oxide was obtained after washing with alcohol.
[0064] The preparation steps of hollow silicon dioxide spheres in this embodiment are as follows:
[0065] (I) Mix 20-25mL of tetraethyl orthosilicate with 12mL of mixed template liquid, raise the temperature to 60℃, stir at 75rpm, and stir for 8min. Then, add 24mL of 3% dilute hydrochloric acid solution to the mixed solution at a rate of 10mL / min, increase the stirring speed to 200rpm for 5min, and then add 20mL of anhydrous ethanol and stir to obtain a sol solution. Put the sol solution into a rubber-tipped dropper, prepare a 250mL beaker, pour 150mL of tetrahydrofuran, add the sol solution dropwise to the tetrahydrofuran, maintain the water bath temperature at 55℃, let stand for 10h, then wash with anhydrous ethanol, dry and filter to obtain silica beads with a diameter of 4mm.
[0066] (II) The silica beads were transferred to a muffle furnace, and the temperature in the muffle furnace was raised to 350°C at a rate of 7°C / min, and kept at this temperature for 25 minutes. The solid matter was then taken out of the muffle furnace, and the temperature was naturally lowered to 45°C. The solid matter was then added back into the muffle furnace, and the temperature was finally raised to 650°C at a rate of 12°C / min, and then kept at this temperature for 2 hours to obtain a sintered product. The sintered product was then transferred to 75 mL of hydrofluoric acid with a molar concentration of 0.05 mol / L, and after being treated for 15 minutes, a silica hollow sphere was obtained.
[0067] Among them, glass fiber (average diameter 9 microns, aspect ratio 300:1). Paraffin wax No. 58 (article number: MF-0005) was provided by Jiangyin Mengfan Rubber & Plastic Trading Co., Ltd. The mixed crosslinking agent is a mixture of diphenylmethane diisocyanate and tritolyl phosphite in a mass ratio of 5:1. The bromoalkyl source is obtained by mixing 1,2-dibromododecane, 1,3-dibromotetradecane, and 1,10-dibromooctadecane in a mass ratio of 1:1.5:3. The mixed solvent is prepared by mixing acetonitrile, potassium carbonate, and pyridine in a mass volume ratio of 75mL:2g:2.5g. The mixed template liquid is prepared by mixing sodium hexametaphosphate, Tween 20, soybean lecithin, and carboxymethyl cellulose in a mass volume ratio of 1.5g:0.3mL:1.25g:0.73g.
[0068] Example 3
[0069] The preparation method of the salt-resistant foam drainage agent used in natural gas development in this embodiment is as follows:
[0070] (1) Add 25 mL of ethylene glycol to 50 g of modified amine oxide, control the temperature to 55 °C, mix evenly, then add 0.2 g of ammonium dihydrogen phosphate and 1 g of dodecyl dimethyl amine oxide, mix to obtain an injection solution. Mix 50 g of the injection solution with 10 g of hollow silica balls, then depressurize the container to 0.03 MPa, adjust the magnetic stirring speed to 50 rpm, return to normal pressure after 1 hour of treatment, and let stand for 30 minutes. The resulting mixture is recorded as M.
[0071] (2) Take 10g of glass fiber and add it to a high-speed crusher, control the speed to 1000r / min, crush for 15min, and obtain chopped glass fiber. Use 20mL of chloroform to disperse the chopped glass fiber, mix it with 50g of No. 58 paraffin wax, heat it to 80℃, and treat it for 30min. Control the magnetic stirring speed to 50rpm, continue stirring for 20min, then add 4.5g of mixed cross-linking agent, increase the stirring speed to 100rpm, continue stirring for 2.5h, then lower the temperature to 60℃ and keep it constant to obtain the sealing liquid. Filter the precipitate of M and add it to the sealing liquid, let it stand for 1h, filter the precipitate again, cool it naturally, wait for the paraffin on the surface of silica to solidify, remove the sticky paraffin, and obtain the anti-salt foam drainage agent for natural gas development.
[0072] The preparation steps of the modified amine oxide in this embodiment are as follows:
[0073] (S01) Take 15g of bromoalkyl source, mix with 12g of dipropylamine, use 200mL of anhydrous ethanol as the reaction solvent, control the reaction time to 8h and the temperature to 65°C, and obtain a tertiary amine intermediate. Then, add 4.2g of sodium carbonate to the system, control the magnetic stirring speed to 100rpm, stir for 15min, filter, take the liquid part, and then add 45mL of 10% hydrogen peroxide solution at a rate of 5mL / min to the system, control the reaction temperature to 85°C, the magnetic stirring speed to 150rpm, react for 2h, perform rotary evaporation, adjust the vacuum degree to 300mbar, the water bath temperature to 70°C, and the rotation rate to 150rpm. After treating for 2h, take the bottom viscous liquid, wash with toluene to remove impurities, and obtain brominated amine oxide.
[0074] (S02) Brominated amine oxide was mixed with 3.6 g of urea, 75 mL of mixed solvent was added, the temperature was controlled at 70°C, the reaction was carried out for 7 hours, and then the solvent was removed by distillation. The modified amine oxide was obtained after washing with alcohol.
[0075] The preparation steps of hollow silicon dioxide spheres in this embodiment are as follows:
[0076] (I) Mix 25 mL of tetraethyl orthosilicate with 13 mL of mixed template solution, raise the temperature to 65 ° C, stir at a magnetic stirring speed of 75 rpm, and stir for 10 minutes. Then, add 25 mL of a 3.5% dilute hydrochloric acid solution to the mixed solution at a speed of 10 mL / min, increase the stirring speed to 250 rpm for 5 minutes, and then add 20 mL of anhydrous ethanol and stir to obtain a sol solution. Put the sol solution into a rubber-tipped dropper, prepare a 250 mL beaker, pour 150 mL of tetrahydrofuran, and drop the sol solution into the tetrahydrofuran dropwise, maintain the water bath temperature at 55 ° C, let it stand for 15 hours, then wash with anhydrous ethanol, dry and filter to obtain silica beads with a diameter of 4 mm.
[0077] (II) The silica beads were transferred to a muffle furnace, and the temperature in the muffle furnace was raised to 350°C at a rate of 8°C / min, and kept at this temperature for 30 minutes. The solid matter was then taken out of the muffle furnace, and the temperature was naturally lowered to 50°C. The solid matter was re-added to the muffle furnace, and finally the temperature was raised to 750°C at a rate of 15°C / min, and then kept at this temperature for 3 hours to obtain a sintered product. The sintered product was then transferred to 100 mL of hydrofluoric acid with a molar concentration of 0.05 mol / L, and after treatment for 30 minutes, a silica hollow sphere was obtained.
[0078] Among them, glass fiber (average diameter 9 microns, aspect ratio 300:1). Paraffin wax No. 58 (article number: MF-0005) was provided by Jiangyin Mengfan Rubber & Plastic Trading Co., Ltd. The mixed crosslinking agent is a mixture of diphenylmethane diisocyanate and tritolyl phosphite in a mass ratio of 5:1. The bromoalkyl source is obtained by mixing 1,2-dibromododecane, 1,3-dibromotetradecane, and 1,10-dibromooctadecane in a mass ratio of 1:1.5:3. The mixed solvent is prepared by mixing acetonitrile, potassium carbonate, and pyridine in a mass volume ratio of 100mL:2g:2.5g. The mixed template liquid is prepared by mixing sodium hexametaphosphate, Tween 20, soybean lecithin, and carboxymethyl cellulose in a mass volume ratio of 2g:0.3mL:1.25g:0.73g.
[0079] Comparative Example 1
[0080] The preparation steps of the modified amine oxide of this comparative example are as follows:
[0081] (S01) Take 15g of bromoalkyl source, mix with 10g of dipropylamine, use 150mL of anhydrous ethanol as the reaction solvent, control the reaction time to 5h and the temperature to 55°C, and obtain a tertiary amine intermediate. Then, add 3.2g of sodium carbonate to the system, control the magnetic stirring speed to 100rpm, stir for 10min, filter, take the liquid part, and then add 35mL of 10% hydrogen peroxide solution by mass to the system at a rate of 5mL / min, control the reaction temperature to 70°C, the magnetic stirring speed to 100rpm, react for 1h, perform rotary evaporation, adjust the vacuum degree to 250mbar, the water bath temperature to 65°C, the rotation rate to 150rpm, treat for 1.5h, take the bottom viscous liquid, wash with toluene to remove impurities, and obtain brominated amine oxide.
[0082] (S02) Brominated amine oxide is mixed with 3 g of urea to obtain modified amine oxide.
[0083] The remaining steps are the same as those in Example 1.
[0084] Comparative Example 2
[0085] The preparation method of the salt-resistant foam drainage agent for natural gas development in this comparative example is as follows:
[0086] (1) Add 25 mL of ethylene glycol to 45 g of modified amine oxide, control the temperature to 45 °C, mix well, then add 0.1 g of ammonium dihydrogen phosphate and 0.5 g of dodecyl dimethyl amine oxide, mix to obtain an injection solution. Mix 60 g of the injection solution with 8 g of hollow silica balls, then depressurize the container to 0.01 MPa, adjust the magnetic stirring speed to 50 rpm, treat for 0.5 h, return to normal pressure, and let stand for 10 min. The resulting mixture is recorded as M.
[0087] (2) Take 20g of cellulose acetate (acetylation degree 35.7%, hydroxyl mass fraction content 4.2%), dry it at 45℃ for 10-15h, then add it to a high-speed pulverizer, control the speed to 1000r / min, and pulverize it for 15min to obtain chopped fibers. Use 20mL of chloroform to disperse the chopped fibers, mix them with 50g of No. 58 paraffin wax, heat them to 80℃, and treat them for 30min. Control the magnetic stirring speed to 50rpm, continue stirring for 20min, then add 4.5g of mixed cross-linking agent, increase the stirring speed to 100rpm, continue stirring for 4.5h, then reduce the temperature to 60℃ and keep it constant to obtain a sealing liquid. Filter the precipitate of M and add it to the sealing liquid, let it stand for 1h, filter the precipitate again, cool it naturally, wait for the paraffin on the surface of silica to solidify, remove the sticky paraffin, and obtain the anti-salt foam drainage agent for natural gas exploitation.
[0088] The remaining steps are the same as those in Example 1.
[0089] Performance testing
[0090] Preparation of 100g / L simulated formation water:
[0091] Weigh 12.87g of calcium chloride, 4.38g of magnesium chloride, and 80.00g of sodium chloride to the nearest 0.01g, dissolve them in distilled water in a beaker, stir well, and transfer to a 1000mL volumetric flask; weigh 2.75g of sodium sulfate to the nearest 0.01g, dissolve them in distilled water in a beaker, stir well, and mix them into a volumetric flask, make up to 1000mL, and shake well for use.
[0092] Preparation of Type II foaming agent solution:
[0093] Weigh 2.5 g of solid foaming agent into a 250 mL beaker, accurate to 0.01 g, dissolve it in 100 g / L simulated formation water, make up to 1000 mL volumetric flask, shake well and set aside.
[0094] In the foaming power experiment, take 212.5mL of foaming agent solution, add 37.5mL of petroleum ether, stir well and then use.
[0095] In the liquid carrying capacity experiment, take 170mL of the foaming agent solution, preheat it in a (65±1)℃ water bath for 15min, then add 30mL of petroleum ether, stir evenly and use.
[0096] Table 1 Performance test items and standards of Examples 1-3 and Comparative Examples 1-2
[0097]
[0098] Test methods for foaming power and liquid carrying capacity
[0099] The test is carried out in accordance with the relevant test methods of GB / T13171.2-2022 and Q / SYCQ17019-2020.
[0100] Table 2 Performance test results of Examples 1-3 and Comparative Examples 1-2
[0101]
[0102] By analyzing Examples 1-3 and Comparative Examples 1-2 and combining with Table 2, it can be seen that the anti-salt foam drainage agent for natural gas exploitation prepared by the embodiment scheme has higher foaming power and liquid carrying capacity data before and after aging than the comparative example. The average foaming starting height and liquid carrying capacity of the embodiment after aging only decreased by about 3.7%-3.8% compared with before aging, and the average 5-minute foaming height decreased by less than 4.5%. Among them, Example 3 has the best comprehensive foaming power and liquid carrying capacity. Compared with the embodiment, the decrease in the two test items of the comparative example after aging is higher than 5%, among which the foaming power of the comparative example 2 decreases by more than 5.8%, and the foaming effect is not stable.
[0103] By analyzing Examples 1-3 and Comparative Examples 1-2 and combining Tables 1 and 2, it can be seen that the anti-salt foam drainage agent for natural gas exploitation prepared by the method of the embodiment meets the enterprise standard requirements and is suitable for industrial production and application.
[0104] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A method for preparing a salt-resistant foam drainage agent for natural gas development, characterized in that: The steps include: (1) Dissolving the modified amine oxide, mixing it with the hollow silica spheres, treating it under reduced pressure for 0.5-1 h, and allowing it to stand at normal pressure to obtain a mixture, which is recorded as M; (2) Crush glass fiber, disperse it in chloroform, mix it with No. 58 paraffin, treat it at 75-80℃ for 10-30min, add mixed cross-linking agent, stir it for 2-2.5h, keep it at 60-65℃ to obtain sealing liquid, filter M to get precipitate, mix it with sealing liquid, let it stand for 0.5-1h, filter it again to get precipitate, and after cooling, obtain anti-salt foam drainage agent for natural gas exploitation; The preparation steps of the modified amine oxide are as follows: (S01) Mix a brominated alkyl source and dipropylamine, dissolve them, react at 55-65°C for 5-8h, add sodium carbonate, stir, filter out the liquid, dropwise add hydrogen peroxide solution, react at 70-85°C for 1-2h, then rotary evaporate, take the bottom viscous liquid, wash and obtain brominated amine oxide; (S02) mixing brominated amine oxide with urea, dissolving in a mixed solvent, reacting at 55-70° C. for 5-7 hours, distilling, and washing with alcohol to obtain a modified amine oxide; The mixed solvent is prepared by mixing acetonitrile, potassium carbonate and pyridine in a mass volume ratio of (50-100) mL: (1.5-2) g: (1.5-2.5) g.
2. The method for preparing a salt-resistant foam drainage agent for natural gas exploitation according to claim 1, characterized in that: In the step (1), the mixed solution obtained by dissolving the modified amine oxide is used as the injection liquid, and the mass ratio of the hollow silica spheres to the injection liquid is 1:(5-7.5).
3. The method for preparing a salt-resistant foam drainage agent for natural gas exploitation according to claim 1, characterized in that: In the step (2), the mixed cross-linking agent is prepared by mixing diphenylmethane diisocyanate and tricresyl phosphite in a mass ratio of 5:
1.
4. A salt-resistant foam drainage agent for natural gas exploitation, prepared by the method for preparing a salt-resistant foam drainage agent for natural gas exploitation according to any one of claims 1 to 3, characterized in that The preparation steps of the hollow silicon dioxide spheres are as follows: (I) Mixing ethyl orthosilicate with a mixed template solution, stirring at 60-65°C, adding a dilute acid solution dropwise, reacting, adding anhydrous ethanol, stirring to obtain a sol solution, and then dropping it dropwise into tetrahydrofuran, with a water bath temperature of 53-60°C, standing for 8-15 hours, filtering and drying to obtain silica beads; (II) Calcine and acid-etch the silica beads to obtain hollow silica spheres.
5. The salt-resistant foam drainage agent for natural gas exploitation according to claim 4, characterized in that: In the step (S01), the alkyl bromide source is obtained by mixing 1,2-dibromododecane, 1,3-dibromotetradecane, and 1,10-dibromooctadecane in a mass ratio of 1:1.5:(2.5-3); the mass ratio of the alkyl bromide source to dipropylamine is 1:(0.67-0.8).
6. The salt-resistant foam drainage agent for natural gas exploitation according to claim 4, characterized in that: In the step (S01), the mass concentration of the hydrogen peroxide solution is 10%-15%.
7. The salt-resistant foam drainage agent for natural gas exploitation according to claim 4, characterized in that: In the step (I), the mixed template solution is prepared by mixing sodium hexametaphosphate, Tween 20, soybean lecithin, and carboxymethyl cellulose in a mass volume ratio of (1-2) g: (0.2-0.3) mL: (1.03-1.25) g: (0.5-0.73) g.
8. The salt-resistant foam drainage agent for natural gas exploitation according to claim 4, characterized in that: In the step (II), the calcination includes primary calcination, cooling, and secondary calcination, and the operation is as follows: Primary calcination: raise the temperature in the muffle furnace to 300-350°C at a rate of 5-8°C / min and keep it at that temperature for 20-30 minutes; Cooling: Take the solid material out of the muffle furnace and cool it down naturally to 45-50℃; Secondary calcination: add the solid material back into the muffle furnace at a rate of 10-15°C / min, raise the temperature to 600-750°C, and then keep the temperature constant for 2-3 hours.
9. The salt-resistant foam drainage agent for natural gas exploitation according to claim 4, characterized in that: In the step (II), the acid etching operation is: using hydrofluoric acid with a molar concentration of 0.05 mol / L for 10-30 min.
Citation Information
Patent Citations
Foam net synergistic solid foam scrubbing agent and preparation method thereof
CN117777985A
Corrosion and scale inhibition foaming drainage agent and preparation method and application thereof
CN104830303A
Method for draining and producing gas by adopting oil-proof foam drainage agent composition
CN109681176A